The metamorphosis of criminal justice : a comparative account - Hodgson, Jacqueline (New York : Oxford University Press, 2020)
The focus of this book is the potentially radical and fundamental changes that are taking place within criminal justice in Britain and in France and the ways that these are driven by wider domestic, European, or international concerns. This metamorphosis away from established values and practices is eroding what were once regarded as core rights and freedoms in the name of efficiency, security, and justice to victims. Beginning with a comparative analysis of adversarial and inquisitorial procedural values and traditions, and an examination of broad trends in domestic and European criminal justice, the book then discusses how the roles of prosecution and defense have been reshaped in different ways in both jurisdictions - both in the text of the law and in their practices.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 30, 2020).
Keywords: Criminal justice, Administration of -- Great Britain; Criminal justice, Administration of -- France; Law; Laws of specific jurisdictions & specific areas of law